Birt-Hogg-Dubé syndrome. State-of-the-art review with emphasis on pulmonary involvement. Issue 3 (March 2015) - Dal Sasso, Aline Amaral; Belém, Luciana Camara; Zanetti, Gláucia; Souza, Carolina Althoff; Escuissato, Dante Luiz; Irion, Klaus Loureiro; Guimarães, Marcos Duarte; Marchiori, Edson
Summary Background Birt-Hogg-Dubé syndrome (BHDS) is a rare, inherited autosomal-dominant disorder characterized by the development of cutaneous lesions, renal tumors, pulmonary cysts, and spontaneous pneumothorax. The gene responsible for BHDS is located on the short arm of chromosome 17 (17p11.2) and codes for the protein folliculin, which is believed to be an oncogene suppressor protein. Methods We reviewed currently published literature on the main characteristics of BHDS. Results Pulmonary cysts and spontaneous pneumothorax are often the presenting manifestations that lead to a final diagnosis in family members affected by the syndrome. Conclusions Certain imaging characteristics of pulmonary cysts, including size and location, can suggest the diagnosis of BHDS based on chest computed tomography alone. The main concern in patients with BHDS is the increased risk of renal carcinoma. The aim of this review is to describe the main pathological, clinical, and imaging aspects of BHDS, ranging from its genetic basis to treatment, with emphasis on pulmonary involvement.